2016
DOI: 10.1007/s00062-016-0517-0
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroradiological Spectra of Adult and Pediatric Medulloblastoma Differ

Abstract: Although the neuroradiological spectrum of medulloblastoma in adults was similar to children, an atypical presentation with inhomogeneous contrast enhancement, more hyperintense signal on T1 and a more hypointense signal on T2-weighted sequences was common. Given the rarity of the tumor, awareness of these differences constitutes a prerequisite to avoid delays in diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In our study, the three most prevalent histological types of PFT were pilocytic astrocytomas (32.71%), medulloblastomas (33.17%), and anaplastic ependymomas (15.42%). These findings are consistent with previous studies, indicating that these types of tumors are the most commonly occurring in the posterior fossa [1,6,23,[26][27][28][29].The prevalence of other tumor types, such as atypical rhabdoid/teratoid tumors, hemangioblastomas, vestibular schwannoma, gangliocytomas of the cerebellum, and meningiomas, was relatively low, accounting for 18-19% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the three most prevalent histological types of PFT were pilocytic astrocytomas (32.71%), medulloblastomas (33.17%), and anaplastic ependymomas (15.42%). These findings are consistent with previous studies, indicating that these types of tumors are the most commonly occurring in the posterior fossa [1,6,23,[26][27][28][29].The prevalence of other tumor types, such as atypical rhabdoid/teratoid tumors, hemangioblastomas, vestibular schwannoma, gangliocytomas of the cerebellum, and meningiomas, was relatively low, accounting for 18-19% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…7 – 9 In light of the recent discovery of molecular subgroups, this heterogeneity can now actually be seen as a normal reflection of significantly different tumour types, and may aid in the imaging diagnosis of medulloblastoma subtypes. 10 Our case report adds important features regarding these heterogeneous imaging aspects.…”
Section: Discussionmentioning
confidence: 72%
“…While SHH tumours have been shown to be laterally localized, WNT tumours are located more paramedially, which is concordant with our findings. 10 Other imaging findings have so far not been correlated with molecular subgroups, probably owing to the low prevalence of medulloblastoma in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…However, Malheiros et al reported that most adult‐onset medulloblastomas occurred in the cerebellar hemisphere, were poorly defined, had slight and heterogeneous contrast enhancement, especially for a classic medulloblastoma, and had cystic appearances on T2‐weighted images 3 . Also, we collected and analyzed the papers about MRI findings of adult‐onset medulloblastoma, which realized that lateral asymmetrical location (76/125, 60.8%) 3‐6 and mass effect (24/26, 92.3%) 3,5,6 could be common characteristics compared to pediatric medulloblastoma in the limited reports. Our case fulfilled the common MRI characteristics of adult‐onset medulloblastoma but was atypical because the tumor was symmetrically located in the paramedian site with no mass effect.…”
Section: Discussionmentioning
confidence: 97%